Hopf bifurcation on one of tumor models - Kavaliauskas, Algis (Lietuvos matematikos rinkinys, 2005)
The article deals with qualitative analysis of model of pulsing tumor. The model is described by the system of second order differential equations. The region of parameters is determined where the Hopf bifurcation of the stationary zero point is possible.
Keywords: pulsing tumor; Hopf bifurcation